Metabolism of dihydroaminopterin and the influence of aminopterin and related derivatives on the metabolism of (−)-5-formyl-tetrahydrofolic acid in Pediococcus cerevisiae - BUHRING, K; FOLSCH, E (Biochimica et biophysica acta, 1976)
[ 3H]Dihydroaminopterin, but not [ 3H]methotrexate or [ 3H]aminopterin, was rapidly taken up by resting cells of Pediococcus cerevisiae and inhibited the uptake of (−)-5-formyl-tetrahydrofolic acid to more than 90% at a concentration of 25 μM. On the other hand 5-formyl-tetrahydrofolic acid inhibited the uptake of dihydroaminopterin to a similar extent. Dihydroaminopterin was metabolized by Pediococcus cerevisiae, but not by Lactobacillus casei, to a compound tentatively identified as dihydroaminopterin diglutamate. Methotrexate or aminopterin at a concentration of 25 μM did not inhibit the uptake of 5-formyl-tetrahydrofolic acid in Pediococcus cerevisiae, but inhibited the conversion of this compound to polyglutamate forms almost completely at a level of 2.5 μM.